Text retrieval for Malaysian Parliament Document using latent semantic indexing technique / Nor Hidayah Ishak - Ishak, Nor Hidayah (2010)
Information retrieval is a tool to perform searching an effectively and efficiently. Document retrieval or text retrieval is a branch of information retrieval where the information is stored in the form of text. According to Tengku Mohd, document retrieval in Information Retrieval Systems (IRS) is generally about understanding of information in the contents of documents (2005). The retrieval outcomes will be more effective if the system more understand the contents of documents (Tengku Mohd, 2005).The rapid growth of text document in Malay language such as parliamentary proceedings, newspaper articles, and academic publications can give harder to find relevant information. Therefore, this research is developed text retrieval prototype using Latent Semantic Indexing on transcribed Malaysian Parliament documents. By using Latent Semantic Indexing (LSI) technique is can speed up the process of searching and retrieving information from text documents. The Malaysian Parliament documents are maintained by House of Parliament. These documents are categorized into House of Commons and House of Lords.